ANALYSIS OF STRATEGIC POSITIONING ON ORGANIZATION PERFORMANCE OF MOBILE TELECOMMUNICATION FIRMS IN NAIROBI COUNTY KENYA - GLORIAH, KUGUN; WANYONYI, Dr. KADIAN WANYAMA; SIALO, MR. FELIX; SANGORO, MR. OSCAR (IJRDO - Journal of Business Management, 2016)
The telecommunications industry has undergone dramatic shifts in its evolution. Since the end ofthe long-distance monopolies in the early 1980s and local monopolies in 1996, the industry hasseen deregulation, innovation strategy, and new market entrants. Furthermore, the study wasgrounded on Diffusion Innovation Theory and the conceptual framework. The study adopted adescriptive and correlational research designs. Target population of this study comprised of12,561 employees from Information Technology, Marketing and Procurement Departments:(Safaricom-6,500, Airtel-1,810 and Orange-4,251. The researcher then purposively select 10managers from Safaricom Company Limited, 10 managers from Airtel and 10 managers fromOrange Kenya. The 109 employees were selected through simple random sampling. Primary datawas collected using questionnaires and interview schedules. The instruments was validated andtested for reliability through pilot testing. Quantitative data was analysed by use of descriptiveand inferential statistics. Qualitative data from the in-depth interviews and focused groupdiscussion were also analyzed and presented appropriately. For the study, the results indicatedthat innovation strategy had a statistically significant strong effect on the performance (R=0.715)and explained 51.2% of its variation (R2=.512, P=0.000). The results indicated that Marketingstrategy had a statistically significant effect on the performance (R=0.773) and explained 59.7%of its variation (R2=.597, P=0.000). The unstandardized regression coefficient (β) value of theMarketing strategy was 0.956 with a t-test of 12.229and significance level of p-value=.000. Theinferential results indicated that transformational leadership had a statistically significant effecton the performance (R=0.452) and explained 30.4% of its variation (R2=.204, P=0.000). Lastly,supply chain integration had significant relationship with the performance of sampledtelecommunication firms in Kenya. This was achieved through affordable cost, conduciveenvironment, distribution of services and clear logistics strategic plan. However, majority of therespondents disagreed that their organization is currently doing business with companies globally